Pro VB 2008 and the.NET 3.5 Platform - Troelsen, Andrew (Apress, 2012)
The initial release of the .NET platform (circa 2001) caused quite a stir within the Visual Basic programming community. One the one hand, many die-hard VB6 developers were up in arms at the major differences between VB6 and Visual Basic .NET (VB .NET). Individuals in this group were a bit stunned to see that VB .NET was not in fact “VB7” (i.e., the same syntax and programming con- structs as VB6 with some new features thrown in for good measure), but something altogether different.